123I‐Metaiodobenzylguanidine Myocardial Scintigraphy in Discriminating Degenerative Parkinsonisms. Issue 5 (7th May 2021) - Catalan, Mauro; Dore, Franca; Polverino, Paola; Bertolotti, Claudio; Sartori, Arianna; Antonutti, Lucia; Cucca, Alberto; Furlanis, Giovanni; Capitanio, Selene; Manganotti, Paolo
ABSTRACT: Background: 123 I‐Metaiodobenzylguanidine ( 123 I‐MIBG) myocardial scintigraphy is a useful technique to differentiate Parkinson's disease (PD) from atypical parkinsonisms, since it is generally abnormal in PD and normal in the latter. Reduction of myocardial MIBG uptake is a supportive feature in the latest PD diagnostic criteria. Objectives: To explore the clinical contribution of myocardial scintigraphy in discriminating different forms of parkinsonisms, especially when atypical features are present. Methods: Forty‐one patients with parkinsonism underwent a 123 I‐MIBG myocardial scintigraphy in our Movement Disorders Center. Disease evolution was reviewed by applying the latest disease criteria for PD, multiple system atrophy (MSA), progressive supranuclear palsy (PSP) and corticobasal syndrome (CBS), as appropriate. Three diagnostic times were defined: T1 (before scintigraphy execution), T2 (immediately after the exam) and T3 (two years later). Early and delayed heart/mediastinum (H/M) ratios and washout rate (WR) were analyzed. Results: Myocardial scintigraphy showed impaired MIBG uptake in 12 out of 15 patients with a definite PD diagnosis, while normal uptake was found in 20 of 26 patients with no‐PD. Early and delayed H/M ratios were significantly lower in PD compared to overall no‐PD patients and MSA patients. 123 I‐MIBG myocardial scintigraphy was abnormal in all PD patients with dysautonomia. After 123 I‐MIBG myocardial scintigraphy (T2), in 9 patients (22%) an improvement of diagnostic accuracy was reached. Conclusions: Diagnostic accuracy of myocardial scintigraphy in distinguishing PD from atypical parkinsonism was suboptimal. Nevertheless, this study confirmed the relevance of 123 I‐MIBG myocardial scintigraphy for the discrimination of PD from atypical parkinsonism, especially when dysautonomic symptoms are present.